Chitosan as a Strategy in the Treatment of Effluent (Research, Society and Development, 2022)
The treatment of effluents requires new methodologies for the treatment of the tailings. One option is the use of natural coagulants. Chitosan has amino groups in the polymeric chains that allow it to act as a cationic polyelectrolyte and present a high density of charges, which are easily adsorbed on negatively charged surfaces, which is the case for most colloidal impurities present in water. Thus, this work used chitosan in the coagulation/flocculation process to remove color, turbidity and suspension of solids, as a strategy in the treatment of effluents. For that, samples of effluents from the textile industry in the of State of Rio Grande do Norte and samples of effluents from stabilization Lagoons in the municipalities of Touros and Santa Cruz were used in the coagulation/flocculation tests using jar-test. The results proved to be efficient for the removal of color, turbidity and suspension of solids from the samples. The best dosages were 22.5 mg/L and 37.5 mg/L for textile industry effluents, 52.5 mg/L and 60 mg/L for Santa Cruz lagoon effluent; 30 mg/L and 37.5 mg/L for effluent from Touros lagoon. It was observed in this work that chitosan presented in an optimal proportion, that is, the addition of more chitosan did not provide greater removal and that it can be used as a coagulant/flocculant in the treatment of effluents from both the textile industry and domestic effluents, replacing the synthetic coagulants or being used together with them.